Independency of regulating RH and O2/CO2 concentration and its effect on the quality of strawberry at 25°C. (21st October 2019) - Wu, Yanhu; Li, Dongli; Fu, Yabo; Liao, Ruijuan; Shi, Jiazi; Wang, Jigang; Xu, Wencai
Abstract: Strawberries have a short postharvest life due to their relatively high water content, high metabolic activity, and susceptibility to microbial rot. Traditional MAP, even antimicrobial film could not avoid strawberry decay at room temperature. To solve this problem, a new passive MAP (PMAP) is proposed in this article. The innovation of the PMAP lies in the special structure of the lid film. The lid film of PMAP consists of two function films, which is paratactic border‐connected. The one film (oxygen permeable film) only allows O2 (or CO2 ) to pass through, and the other film (water vapor permeable film) only allows water vapor to pass through. Thus, the O2 concentration and relative humidity in the PMAP could be controlled by the area and gas permeability of the dual pieces function films, respectively and independently. In this way, the PMAP could establish a modified atmosphere with any relative humidity without any change in O2 concentration. Results show that the O2 concentration and relative humidity in headspace can be accurately controlled by the designed PMAP. The PMAP could prolong the shelf life of strawberry to 5–6 days at 25°C and maintain the excellent taste, special flavor, good appearance, and nutrition. Practical applications: In the packaging system, the area of the different functional films required can be calculated from the physiological effects of the strawberry, which in turn can independently control the physiological strength of the strawberry and RH in the headspace by controlling the area of different functional films. This will extend the shelf life of the retail strawberry. Not only that, but our design can be applied to another fruit packaging by simply selecting the right functional film. In addition, if we want to achieve other functions, such as antibacterial effects, simply add an antibacterial film to our packaging system. And this does not affect the headspace and humidity because they work completely independently. Therefore, our design has important practical significance for the preservation of fruits and vegetables. Abstract :